Direct and Indirect Recycling Strategies of Expired Oxytetracycline for the Anode Material in Lithium Ion Batteries - Hou, Hongying; Dai, Zhipeng; Liu, Xianxi; Yao, Yuan; Yu, Chengyi; Li, Dongdong (Frontiers in Materials, 2019)
It is well known that the antibiotics inhibit the wide spread of various infectious diseases and guarantee the life safety of many patients. However, various waste antibiotics into the environment also posed the great challenges of the environmental contamination and the ecological poison. Unreasonable disposal of expired antibiotics is one of the main sources of waste antibiotics in the ecological environment. For this reason, in order to focus on the circular economy of such highly refined medical grade chemicals, expired oxytetracycline was recycled for the anode active material in lithium ion batteries (LIBs) by direct and indirect strategies. That is, it was directly used as the anode active material or recycled by two-step carbonization for LIBs anode. Furthermore, the effect of these two strategies on the electrochemical performances was also discussed. Both anode materials showed their individual advantages and high feasibility for LIBs anode. For example, both them delivered the satisfactory Li-storage performances. Additionally, the direct route possessed lower recycling cost and high recovery rate, while the application range of carbon material in the indirect route was broader.